PERBANDINGAN KINERJA PASAR MODAL SYARIAH DAN KONVENSIONAL : SUATU KAJIAN EMPIRIS PADA PASAR MODAL INDONESIA - Budi Setiawan (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this study is to investigate the performance of syariah and conventional stock market in Indonesia. This paper uses Jakarta Islamic Index (JII) to represent syariah stock market and Jakarta Composite Index (JCI) to represent conventional stock market. The Treasury bill rate and the MSCI World index are used as risk free rate and stock market benchmark. Daily data were divided into five periods such as pre-asian financial crisis, during asia financial crisis, pre-subprime mortgage financial crisis, during the subprime mortgage financial crisis, and full sample period. We use three risk adjusted performance measures: Sharpe ratio, Treynor ratio, and Jensen alpha. This study shows that the conventional stock market produced more return compared to syariah in all sample periods.Key words: Islamic stock market; conventional stock market; Sharpe Ratio, Treynor Ratio, Jensen alpha